2019
DOI: 10.1159/000499283
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Testicular Papaverine Injection for Testicular Salvage after Blunt Testicular Trauma: A Case Report

Abstract: Blunt trauma is the most common mechanism of injury to the scrotum and testicle. Surgical exploration with primary repair, hematoma evacuation, and de-torsion are common surgical interventions. A 20-year-old male with no previous medical history presented after a high-speed motor vehicle collision. Ultrasonography demonstrated heterogeneous changes of the tunica albuginea and decreased arterial flow to bilateral testicles. He was subsequently taken to the operating room for surgical exploration, which revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 9 A novel technique, as utilized in our case above, involving apposition of the free edges of the tunica vaginalis was reported by Molokwu et al, 8 in which they demonstrated viability and stability in testes size 3 months post-operatively. In a recent case report by Keating et al, 10 they suggest the use of Papaverine as a form of salvage therapy for testicular rupture associated with inadequate perfusion. Papaverine has been utilized in subarachnoid hemorrhage to improve cerebral arterial flow but few studies are available to suggest a role for testicular hypoperfusion and therefore will warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 A novel technique, as utilized in our case above, involving apposition of the free edges of the tunica vaginalis was reported by Molokwu et al, 8 in which they demonstrated viability and stability in testes size 3 months post-operatively. In a recent case report by Keating et al, 10 they suggest the use of Papaverine as a form of salvage therapy for testicular rupture associated with inadequate perfusion. Papaverine has been utilized in subarachnoid hemorrhage to improve cerebral arterial flow but few studies are available to suggest a role for testicular hypoperfusion and therefore will warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular trauma is a relatively uncommon urological emergency that can lead to significant morbidity if not managed promptly and effectively [ 1 ]. Testicular trauma, although relatively rare, can occur due to various causes such as sports injuries, accidents, or direct blows to the groin region [ 2 ]. In severe cases, where the testicles are extensively damaged and cannot be salvaged, the surgical removal of one or both testicles, known as orchiectomy, may be considered [ 3 ].…”
Section: Introductionmentioning
confidence: 99%